PENGARUH ORIENTASI PASAR, ORIENTASI KEWIRAUSAHAAN DAN STRATEGI BERSAING TERHADAP KINERJA PENJUALAN HOME INDUSTRY ANYAMAN BAMBU (Studi Pada Produk Peralatan Rumah Tangga Anyaman Bambu Desa Cibuyur, Pemalang) - Sus wanti; Wahyu Hidayat (Universitas Diponegoro, 2017)
Bamboo is a plant of Indonesian society that has been widely known and holds a very important role in people's lives. Bamboo handicrafts made in order to meet the needs of the household appliance. Competition bamboo products occur both inside and outside the city are very tight even competition ensued with substitute goods such as plastic and glass. Conditions of tight competition makes producers of woven bamboo should further enhance the value of the function and form of the bamboo. This research aims to determine the effect of market orientation (X1), entrepreneurial orientation (X2) and competitive strategy (X3) impact on sales performance (Y) home industry of woven bamboo in village Cibuyur subdistrict Warungpring province Pemalang. The population in this research are all producers of woven bamboo in village Cibuyur. The sample in this research was 50 respondents who produces woven bamboo taken by sampling method saturated. Data collection is done by using a questionnaire. This type of study used survey research of explanatory. The measured of scale is using Likert scale. In the analysis data using the validity, reliability, a correlation coefficient, the determine coefficient, simple linear regression regression analysis linear multiple, t test, f test by using the SPSS 16.0 tools. The results show variable market orientation, competitive strategy and sales performance had categorization a enough answer, while the entrepreneurial orientation is the agree answer. The influence market orientation of the sales performance t count (11,258) > t table (2,0106), there is no influence entrepreneurial orientation of sales performance t count (1,919) < t table (2,0106), influence competitive strategy of the sales performance t count (12,192) > t table (2,0106) and influence market orientation, entrepreneurial orientation and , competitive strategy of the sales performance an f count (61,767) > F table (2,81). The conclusion all of variable independent in this study had influence on variable depend in simultaneous, while market orientation and competitive strategy had influence on sales performance in partial. Producers of woven bamboo Cibuyur village, Pemalang must improve its business spirit, thus created a product capable of competing in the market and continued demand by consumers